Cerebellar Dizziness and Vertigo: Etiologies, Diagnostic Assessment, and Treatment - Zwergal, Andreas; Feil, Katharina; Schniepp, Roman; Strupp, Michael (Seminars in Neurology, 2020)
Cerebellar dizziness and vertigo account for approximately 10% of diagnoses in a tertiary dizziness center. This term summarizes a large group of disorders with chronic (degenerative, hereditary, acquired cerebellar ataxias), recurrent (episodic ataxias), or acute (stroke, inflammation) presentations. Key to the diagnosis is a comprehensive examination of central ocular motor and vestibular function. Patients with cerebellar dizziness and vertigo usually show a pattern of deficits in smooth pursuit, gaze-holding, saccade accuracy, or fixation-suppression of the vestibulo-ocular reflex. Central fixation nystagmus (e.g., downbeat nystagmus), gaze-evoked nystagmus, central positional nystagmus, or head-shaking nystagmus with cross-coupling (i.e., horizontal head shaking causing inappropriate vertical nystagmus) occurs frequently. Overlap syndromes with peripheral vestibular disorders, such as cerebellar ataxia, neuropathy, and vestibular areflexia, exist rarely. Posturography and gait analysis can contribute to diagnostic differentiation, estimation of the risk of falls, as well as quantification of progression and treatment effects. Patients with cerebellar dizziness and vertigo should receive multimodal treatment, including balance training, occupational therapy, and medication.
Keywords: cerebellar disorders; downbeat nystagmus; ocular motor disorders; aminopyridines; acetyl-leucine